A report of a patient with duplication of 7p13←pter and deletion of 2p23←pter due to a maternal 2p;7p translocation - (:unkn) unknown (My University, 2009)
We report a patient with severe developmental delay, failure to thrive microbrachycephaly, large anterior fontanel, ocular hypertelorism, broad nasal bridge, low-set ears, long philtrum, micrognathia, partial cleft palate, broad distal digits, abnormal palmar creases, joint contractures, and cardiovascular anomaly. Cytogenetic analysis with high resolution chromosome banding showed an unbalanced karyotype of 46,XX, der(2)t(2;7)(p23;p13) originating from a maternal balanced translocation. Our patient showed a duplication of 7p13→pter and a deletion of 2p23→pter. Our analysis suggests that duplication 7p is associated with a recognizable characteristic phenotype.
Keywords: 2 p deletion; 7p duplication; Multiple congenital anomaly syndrome